Implementasi Permenkumham Nomor 32 Tahun 2018 di Rumah Tahanan Negara Kelas IIB Bangkalan Ditinjau dari Aspek Kualitas Hidup Narapidana Lanjut Usia - Firmansyah, Fiqi Rheza; Subroto, Mitro (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
A Detention Center is a facility for the rehabilitation of inmates, primarily conducted by correctional officers. The occupants of Detention Center also encompass various age categories, one of which is elderly inmates. Elderly inmates constitute a vulnerable group distinct from those in the productive age range. Minister of Law and Human Rights Regulation No. 32 of 2018 concerning Treatment for Detainees and Elderly Inmates stipulates the necessity of fulfilling the needs of elderly detainees or inmates to maintain their physical, mental, and social well-being. Despite the curtailment of inmates' freedom and mobility, Detention Center is obligated to execute rehabilitation and ensure the fulfillment of specific rights for elderly inmates, aiming to enhance their quality of life. This study aims to ascertain an overview of the quality of life and the challenges in meeting the quality of life for elderly inmates. The research employs a qualitative approach with data collection techniques involving interviews, observations, and documentation. The investigation was conducted at Class IIB Bangkalan Detention Center. The findings of the study indicate that the fulfillment of specific rights for elderly inmates has not been optimally executed in terms of physical healthcare service, psychological support, rehabilitation activities, social interactions, environment, and spiritual well-being of elderly inmates.